PENGARUH PUPUK KANDANG SAPI DENGAN BIODEKOMPOSER DAN PUPUK ANORGANIK TERHADAP EFISIENSI SERAPAN K DAN HASIL TANAMAN PADI (Oryza sativa L.) DI LAHAN SAWAH PALUR SUKOHARJO - Sri Hartati; Jauhari Syamsiyah; Hery Widijanto; Moh. Arief Bonis S (Faculty of Agriculture, Universitas Sebelas Maret, 2009)
Title : The Effect of Cow Manure with Biodecompocer and Inorganic Fertility to Efficiency of K Absorption and Yield of Paddy (Oryza sativa L.) on Paddy Field Palur Sukoharjo. This research was conducted from January–August 2008 in paddy field, Palur Sukoharjo. The aim of this research were to know the effect of cow manure with Biodecompocer and inorganic fertilizer to K uptake efficiency and the rice yield (Oryza sativa L.) in paddy field Palur Sukoharjo. This research used Randomized Completely Block Design (RCBD) with two factors. The first factor was dosage cow manure consist of 7 levels i.e.: B0 (no cow manure), B1 (2.5 t.ha-1cow manure), B2 (5 t.ha-1 cow manure), B3 (2.5 t.ha-1 +stardec), B4 (5 t.ha-1+stardec), B5 (2.5 t.ha-1 +earthworm), B6 (5 t.ha-1 +earthworm). The second factor was Inorganic fertilizer consist of 3 levels i.e.: (without inorganic fertilizer) A0; (Urea 150 kg.ha-1, ZA 50 kg.ha-1, SP36 dosage 75 kg.ha-1 and KCl 50 kg.ha-1) A1; and (Urea 300 kg.ha-1, ZA 100 kg.ha-1, SP36 150 kg.ha-1 and KCl 100 kg.ha-1) A2. Data was analyzed with F-tested level 1% and 5% or Kruskal Wallis test, and continued with Duncan Multiple Range Test 5% (DMRT 5%) or mood median, and correlation test to know relation between observation variable. The result of this research shows that the highest efficiency of K uptake was achieved at 2.5 t.ha-1 cow manure+stardec and Urea 300 kg.ha-1, ZA 100 kg.ha-1 , SP36 150 kg.ha-1 and KCl 100 kg.ha-1 its 4.67%. The highest weight of 1,000 seed was achieved at 5 t.ha-1 cow manure+earthworm and without inorganic fertilizer its 28.79 gr. The highest weight of dry yield rice was achieved (GKG) at 5 t.ha-1 cow manure+stardec and Urea 150 kg.ha-1, ZA 50 kg.ha-1, SP36 75 kg.ha-1 and KCl 50 kg.ha-1) its 11.5 kg.18 m -2 6.39 t.ha-1. Keywords: cow manure, biodecomposer, K Efficiency, paddy